Exclusive safeguards and technology transfer: Subcontracting agreements in Eastern Europe's car component industry - H. Peter Møllgaard; Jochen Lorentzen (Copenhagen Business School (CBS), Department of Economics, 2002)
We study the rationale for the use of exclusivity to protect transfer of technology in subcontracting agreements. The legal possibility arises through the EU Notice on Subcontracting. Empirically, the link between exclusive agreements and technology transfer among firms in the automotive supply industry in EU candidate countries is surprisingly weak, although with exclusive-supply or exclusive-buying clauses in subcontracting agreements upstream transfer of technology is more likely. Exclusive agreements are often reciprocal, and are typically passed on. Downstream firms are more likely to face and use vertical restraints. Technology trickles upstream: Multinational final assemblers transfer more technology than lower-tier suppliers.
hdl:10398/7527
Keywords: D23; D40; K12; L14; L42; L62; 330; Transfer of technology; subcontracting; exclusive agreements; automotive supply industry; vertical restraints